2019
DOI: 10.4103/jfmpc.jfmpc_462_19
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of health services in Tenali Mandal, Andhra Pradesh- A cross-sectional study

Abstract: Introduction:India has a plurality of health care with different systems of medicine delivered by government and local bodies in hospitals and clinics. Public hospitals provide 60% of all hospitalizations, while the private sector provides 75% of all routine care. Utilization is the actual attendance by the members of the public at health care facilities, which measures the number of visits per year or the number of people with at least one visit during the previous year, serves as an important tool and acts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Road access, travel time to medical facilities (Yaddanapalli et al. , 2019 ), and the expense of transit have all been identified as major obstacles to HSU for women in a number of studies (Brownson and Eyong, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Road access, travel time to medical facilities (Yaddanapalli et al. , 2019 ), and the expense of transit have all been identified as major obstacles to HSU for women in a number of studies (Brownson and Eyong, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported road access (Brownson and Eyong, 2020 ), distance to health care centers, and transportation costs as significant barriers to HSU among women (Yaddanapalli et al. , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…a total of 100 individuals from each site were selected resulting in sample size of 1500 and for the age groups of 5 years, 12 years, and 15 years the questionnaire was administered to their parents/guardians. [ 6 ]…”
Section: Methodsmentioning
confidence: 99%